ECONOMIC ASSESSMENT OF SOME SEED TREATMENT MATERIALS ON THE MANAGEMENT OF DOWNY MILDEW ON SELECTED PEARL MILLET CULTIVARS IN MAIDUGURI AND GOMBE, NIGERIA (FULafia Journal of Science and Technology, 2019)
A field trial was conducted at Maiduguri and Gombe towns to assess the economic implications of All Star 40DS, Silicon dioxide (SiO2) and Diatomaceous Earth (DE) on the management of downy mildew (Sclerosporagraminicola(Sacc.) Schroet) in selected pearl millet cultivars. Split plot design was used where three cultivars (SOSAT-C88, Ex-Borno and LCIC-7902) were assigned to main plots while four seed treatment materials (SiO2, DE, SiO2 + DE, All Star 40DS) and control to sub plots and replicated four times.. The results obtained showed that in Maiduguri, all Star 40DS had the highest net benefit (₦ 114,617.86) and marginal rate of returns (1.20), followed by SiO2 + DE which gave the net benefit of (N 99, 663.57) and marginal rate of returns (1.00) while the control had the lowest net benefit (₦ 40, 617.86 ) and marginal rate of returns (0.40). The result of the combined analysis also showed that all the seed treatment applications translated into gain except with the control. There were also gains of ₦ 0.33, ₦ 0.21 and ₦ 0.15 from the application of All Star and SiO2 + DE respectively and loss of ₦ 0.19 from the control for every ₦ 1.00 naira that was spent. From the present results, SiO2 + DE treatment can therefore be used as an alternative to manage downy mildew of pearl millet as it is cost-effective, available and ecofriendly.